Pengaruh Jenis Kemasan Dan Lama Penyimpanan Terhadap Karakteristik Mutu Bunga Telang (Cloria Ternatea) Kering - Hotman Manurung; Benika Naibaho; Topma Boang Manalu; NDM Romauli (Department of Agricultural Engineering, Syiah Kuala University, 2023)
Abstract The increasing variety of benefits of the butterfly pea flower requires the availability of dried butterfly pea flowers to replace fresh butterfly pea flowers. A study has been carried out on